MENGATASI BULLYING : PENDEKATAN HOLISTIK UNTUK KESEHATAN MENTAL DI LINGKUNGAN SEKOLAH - Lutfiatul Laili Arrohmati; Richardo Yobel Ritonga; Shandra Agusti Pamungkasari (MERDEKA : Jurnal Ilmiah Multidisiplin, 2024)
This study uses secondary data collected from various sources including books, journal articles, and legal documents to analyze and interpret the subject of the study regarding transfer office technology (TTO). The qualitative desk research approach was chosen because of its relevance to the digital era and technological advances, which facilitate data access and analysis. In addition, this study also involved community service activities carried out at SMP Pancasila Jombang, aimed at socializing anti-bullying, especially cyberbullying, to students. This activity includes education about the impact of bullying, prevention techniques, and anti-bullying declarations followed by students. The results of the socialization showed an increase in students' understanding of bullying and its impacts, as well as an emphasis on the need for a holistic approach in supporting children's mental health. This approach involves a combination of psychological interventions, social support, and mental health promotion, as well as an emphasis on the active involvement of children in their care. Continuous evaluation of the intervention and adjustment of strategies are needed to ensure its effectiveness. Prevention and early intervention programs in schools are essential to address bullying and support students' overall mental health.